Development of fast image analysis technique for All-Sky images - Sharma, A.K.; Nade, D.P.; Nikte, S.S.; Ghodpage, R.N.; Patil, P.T.; Rokade, M.V.; Vhatkar, R.S.; Gurubaran, S. (My University, 2014)
This article describes the possibility of using the fast image analysis technique for qualitative and quantitative analysis of equatorial plasma bubble obtained using All-Sky imager (ASI) data. Automated image processing (generally) is useful for identification of equatorial plasma bubbles (EPBs) and its parameters. We have developed a fast (and efficient) analysis technique essential to study the data of images. The present work reports the results of a statistical study of the zonal plasma bubble velocities using nightglow OI 630.0 nm emission data, acquired by ASI (FOV 140°) at the low-latitude station Kolhapur (16.42°N, 74.2°E and 10.6°N dip lat.). Based on the observations of 15 nights made in January 2012, we have determined the velocity of EPB using our new method. The daily mean values of the EPB velocity match well with those of the earlier studies made at Kolhapur. We have found that, generally, the mean zonal drift velocities of the plasma bubbles tend to decrease with local time (after midnight). The most significant finding from this work is that the calculated velocities of plasma bubble using fast and scanning methods are nearly equal.
Keywords: All sky imager; Equatorial plasma bubbles; Nightglow emissions; Zonal drift velocity